Tomographic Image of Shear Wave Structure of NE India Based on Analysis of Rayleigh Wave Data - Kumar, Amit; Kumar, Naresh; Mukhopadhyay, Sagarika; Klemperer, Simon L. (Frontiers in Earth Science, 2021)
The major scientific purpose of this work is to evaluate the geodynamic processes involved in the development of tectonic features of NE India and its surroundings. In this work, we have obtained tomographic images of the crust and uppermost mantle using inversion of Rayleigh waveform data to augment information about the subsurface gleaned by previous works. The images obtained reveal a very complicated tectonic regime. Bengal Basin comprises a thick layer of sediments with thickness increasing from west to east and sudden steepening of the basement on the eastern side of the Eocene Hinge zone. The nature of the crust below the Bengal Basin varies from oceanic in the south to continental in the north. Indo-Gangetic and Brahmaputra River Valleys comprise of ~5-6 km thick sediments. Crustal thickness in the higher Himalayas and southern Tibet is ~70 km but varies between ~30 km and ~40 km in the remaining part. Several patches of low-velocity medium present in the mid-to-lower crust of southern Tibet along and across the major rifts indicate the presence of either partially molten materials or aqueous fluid. Moho depth decreases drastically from west to east across the Yadong-Gulu rift indicating the complex effect of underthrusting of the Indian plate below the Eurasian plate. Crust and upper mantle below Shillong Massif and Mikir Hills are at shallow level. This observation indicates that tectonic forces and thermal inequilibrium contribute to the uprising of the Massif.